Healthy Dads, Healthy Kids UK, a weight management programme for fathers: feasibility RCT. Issue 12 (10th December 2019) - Griffin, Tania; Sun, Yongzhong; Sidhu, Manbinder; Adab, Peymane; Burgess, Adrienne; Collins, Clare; Daley, Amanda; Entwistle, Andrew; Frew, Emma; Hardy, Pollyanna; Hurley, Kiya; Jones, Laura; et al.
Abstract : Objective: To assess (1) the feasibility of delivering a culturally adapted weight management programme, Healthy Dads, Healthy Kids United Kingdom (HDHK-UK), for fathers with overweight or obesity and their primary school-aged children, and (2) the feasibility of conducting a definitive randomised controlled trial (RCT). Design: A two-arm, randomised feasibility trial with a mixed-methods process evaluation. Setting: Socioeconomically disadvantaged, ethnically diverse localities in West Midlands, UK. Participants: Fathers with overweight or obesity and their children aged 4–11 years. Intervention: Participants were randomised in a 1:2 ratio to control (family voucher for a leisure centre) or intervention comprising 9 weekly healthy lifestyle group sessions. Outcomes: Feasibility of the intervention and RCT was assessed according to prespecified progression criteria: study recruitment, consent and follow-up, ability to deliver intervention, intervention fidelity, adherence and acceptability, weight loss, using questionnaires and measurements at baseline, 3 and 6 months, and through qualitative interviews. Results: The study recruited 43 men, 48% of the target sample size; the mean body mass index was 30.2 kg/m 2 (SD 5.1); 61% were from a minority ethnic group; and 54% were from communities in the most disadvantaged quintile for socioeconomic deprivation. Recruitment was challenging. Retention at follow-up of 3 and 6 months was 63%. Identifying delivery sites and appropriately skilled and trained programme facilitators proved difficult. Four programmes were delivered in leisure centres and community venues. Of the 29 intervention participants, 20 (69%) attended the intervention at least once, of whom 75% attended ≥5 sessions. Sessions were delivered with high fidelity. Participants rated sessions as 'good/very good' and reported lifestyle behavioural change. Weight loss at 6 months in the intervention group (n=17) was 2.9 kg (95% CI −5.1 to −0.6). Conclusions: The intervention was well received, but there were significant challenges in recruitment, programme delivery and follow-up. The HDHK-UK study was not considered feasible for progression to a full RCT based on prespecified stop–go criteria. Trial registration number: ISRCTN16724454 .